A review of poly(3, 4-ethylenedioxythiophene) and its composites-based electrochemical sensors for dopamine detection. Issue 4 (4th March 2021) - Cogal, Sadik
ABSTRACT: Dopamine (DA) is biologically important molecule, which plays a vital role in hormonal, renal, cardiovascular, and central nervous systems. Since abnormal level of this biological molecule leads to several diseases, its accurate and fast monitoring is of great importance for clinical diagnosis and treatment. The electrochemical approaches have become of significant interest to fulfill the requirements of DA detection. The electrode modifications play a crucial role in sensitive and selective detection of DA. This review presents the progress of poly(3, 4-ethylenedioxythiophene) (PEDOT)-based materials modified electrodes for electrochemical determination of DA in the presence of interferents such as AA and UA. Graphical abstract: